Situation Report: Hungary, 8 December 1964 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Forthcoming CC Session to Deal with Factors Hampering Progress Changes in the Ministry of Interior Hungarian Party Delegation to Yugoslav Party Congress Austro-Hungarian Relations Hungarian-Swiss Property Claims Talks Hungarian-United States Talks Hungarian Fresh- and Processed Vegetables and Fruit Supplies to USSR